Tanzania - Public Expenditure Review (PER) of the Water Sector - World Bank (Washington, DC, 2012)
Tanzania initiated a forward-looking National Water Policy (NAWAPO-2002) to promote an integrated approach to water resources management and improve water supply and sanitation service (WSS) delivery in both urban and rural areas. To do this, the Government initiated in 2004 a doubling of budget allocations to the water sector from $60 million to $120 million. It also has shifted the role of the Ministry of Water and Irrigation (MOWI), moving from central control of water projects to facilitating and funding projects and strengthening sector institutions and capacity at the national, basin, and local government levels. Much of Tanzania's capital budget goes to fund water supply infrastructure, largely driven by the focus on achieving the millennium development goals. Donors supply most of the capital funding and are coordinating funds through a Sector Wide Approach to Planning (SWAp) to maximize effectiveness. This public expenditure review focuses on the quantity and quality of Tanzania's public funding process to assess how well budget allocations for the water sector actually translate into better water and sanitation service delivery.